Secondary minerals of the Jachymov (Joachimsthal) ore district - Ondrus,P.; Veselovsky,F.; Hlousek,J.; Skala,R.; Vavrin,I.; Fryda,J.; Cejka,J.; Gabasova,A. (Journal of the Czech Geological Society, 1997)
Two hundred and seven secondary mineral species are described and/or referenced. Approximately seventy secondary minerals were known from the district before the present study. All known reliable data on the individual secondary minerals from Jachymov are presented. New and more complete X-ray powder diffraction data for compreignacite, irhtemite, lavendulan, lindackerite, masuyite, mcnearite, metaschoepite, mottramite, rabbittite, rabejacite, richetite, sodium-zippeite, voglite, zellerite, zippeite, and zykaite are presented. A list of secondary minerals arranged according to chemical composition and list of “non-secondary” minerals are included at the end of this paper.
Keywords: secondary minerals; new data; Jachymov; encyclopaedia